Real‐time study of transients during high‐temperature creep of an Ni‐base superalloy by far‐field high‐energy synchrotron X‐ray diffraction. Issue 5 (9th August 2018) - Tréhorel, Roxane; Ribarik, Gabor; Schenk, Thomas; Jacques, Alain
Abstract : A far‐field double‐crystal diffractometry technique using synchrotron X‐rays was employed to record lattice parameters of an Ni‐base single‐crystal superalloy with a high frequency (every 7 s) during an in situ creep test. Diffraction scans reveal the presence of subgrains. This article describes this technique and the associated data processing to obtain results that open new scientific opportunities to follow crystalline materials in real time. Abstract : The high‐temperature mechanical behavior of single‐crystal Ni‐base superalloys has been formerly studied by in situ triple‐crystal synchrotron X‐ray diffractometry (TCD). However, the 1/300 s recording frequency does not allow real‐time tests. It is shown here that real‐time monitoring is possible with far‐field diffractometry in transmission. The use of a far‐field camera enables one to follow a diffraction spot with high angular precision and high recording speed. This technique allows measurement of the mechanical response of an AM1 Ni‐base single‐crystal superalloy following steep load jumps and relaxations during high‐temperature creep tests. Local crystal misorientation is revealed and rafting (oriented coalescence) is examined. This new technique is compared with TCD, in order to highlight its benefits and drawbacks.